Christine Brooke-Rose: motes, beams and the horse's mouth. Issue 2 (7th February 2018) - White, Glyn
ABSTRACT: This essay draws on personal correspondence with the Christine Brooke-Rose during the latter stages of her career and discusses her ambivalent status as theoretically 'dead' but still living both inside and outside the academy. In particular, the essay engages with Brooke-Rose's Thru, ambiguity, interpretation, the novel's relationship to contemporary theory and the exceptional nature of this author's critical and creative legacies.